PENGARUH PARTISIPASI ANGGARAN DAN ASIMETRI INFORMASI PADA SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMODERASI - Saputra, Dody Cipta; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi, 2017)
The purpose of this study to determine how the influence of budget participation and asymmetry of information on budgetary slack and how committed the organization can affect the relationship of budget participation and information asymmetries in the three to five-star hotel in the city of Denpasar. This study was performed on 18 three to five star hotels in Denpasar by using the technique of questionnaires as the data collection method. Total population used a total of 106 managers by using purposive sampling method of sampling. The analysis technique used is multiple linear regression and moderated regression analysis (MRA). Based on the results of research conducted known that budgetary participation and information asymmetry positive influence on budgetary slack. Organizational commitment can not moderate positive relationship of budget participation on budgetary slack, but the commitment the organization could weaken the positive relationship asymmetry of information to the budgetary slack.